The Role of Sociology of Law in Realizing Social Justice: A Socio-Legal Perspective - Riyan Adnan Wahyudi; Amirullah; Muh. Ramli; Aslan Syah Mattulanreng (Pustaka Digital Indonesia, 2026)
This study examines the role of the sociology of law in realizing social justice through a socio-legal perspective. Sociology of law views law not merely as a set of formal and written norms, but as a social institution that is closely intertwined with societal values, culture, and power relations. The objective of this research is to analyze how legal systems can effectively promote social justice by considering the social, economic, and cultural contexts in which they operate. This study employs a normative legal research method combined with a conceptual and sociological approach, focusing on the interaction between law in the books and law in action. The findings indicate that the realization of social justice is not solely determined by the quality of legislation, but also by factors such as legal awareness, legal culture, access to justice, and the role of law enforcement institutions. Sociology of law plays a significant role in identifying gaps between normative legal provisions and their implementation in society, particularly in relation to vulnerable and marginalized groups who often face structural barriers in accessing justice. Furthermore, the socio-legal approach contributes to the development of responsive and inclusive legal policies that prioritize substantive justice over formal equality. In conclusion, sociology of law serves as a crucial analytical and practical framework in bridging the gap between legal norms and social reality. By integrating social perspectives into legal processes, law can function more effectively as an instrument of social engineering and a means to achieve equitable and sustainable social justice for all members of society.